2. CLINICAL FEATURES AND RELATED FACTORS OF PITYRIASIS ALBA AT THE NATIONAL HOSPITAL OF DERMATOLOGY AND VENEREOLOGY (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate certain related factors and clinical characteristics of pityriasis alba in patients at the National Hospital of Dermatology and Venereology from September 2024 to August 2025. Subjects and methods: A prospective cross-sectional descriptive study was conducted on 100 patients diagnosed with pityriasis alba who visited and were treated at the National Hospital of Dermatology and Venereology from September 2024 to August 2025. Results: Among the 100 patients surveyed, the majority were aged 6 to 18 years (82%) and had Fitzpatrick skin type IV (71%). The proportion of male patients was slightly higher than female (55% vs. 45%). Lesions were predominantly localized on the face (87%) and commonly developed during the winter season (49%). Clinically, 63% of patients presented with fine scaling, and only 6% reported pruritus. The average disease duration was 8.17 months, with nearly half of the patients affected for less than 6 months. Most patients (82%) had no history of atopic conditions.Conclusion: The study indicates that pityriasis alba predominantly affects children and adolescents, particularly those with darker skin phototypes. The lesions are typically characterized by ill-defined hypopigmented macules covered with fine, delicate scales, most commonly localized on the facial region. The condition tends to manifest more frequently during the winter months. Furthermore, evidence suggests a significant association between pityriasis alba and a personal history of atopic disorders, notably atopic dermatitis.
Keywords: Pityriasis alba, clinical characteristics, National Hospital of Dermatology and Venereology